Indonesia’s Low-Cost Carrier Competitive Landscape: An Analysis of 7 P’s - Abdurrahman, Vidi; Aprianingsih, Atik (Journal Integration of Management Studies, 2025)
This study examines the competitive strategies of four leading low-cost carriers (LCCs) operating in Indonesia—Lion Air, Citilink Indonesia, Indonesia AirAsia, and Super Air Jet—through the lens of the 7Ps marketing mix framework. Amidst intensifying competition and evolving passenger expectations, Indonesian LCCs must now differentiate beyond price. Using a qualitative-comparative approach, the research analyzes how each airline performs across seven dimensions: Product, Price, Place, Promotion, People, Process, and Physical Evidence. Data were collected from secondary sources, including official airline websites, mobile application ratings, national transportation statistics, and the Top Brand Index 2024. Findings reveal distinct strategic postures among the carriers. Citilink and Indonesia AirAsia lead in balancing affordability with service quality and digital integration, while Super Air Jet positions itself as a youthful, brand-driven entrant. Lion Air, though dominant in market share, continues to face challenges in service consistency and customer experience. The study highlights that operational maturity, service delivery, and human capital are critical for sustained competitiveness. The analysis also demonstrates the increasing importance of customer-facing digital systems and physical branding as sources of perceived value in a low-cost context. This research contributes to the growing body of literature on service marketing in aviation and provides strategic insights for airline managers seeking differentiation in price-sensitive markets. Future studies are encouraged to integrate passenger perspectives and explore the role of sustainability in LCC strategies.